Acute hoarseness in severe heart failure: Ortner's Syndrome - Gavrić Jelena; Valjarević Svetlana; Jovanović Anđelina; Jovanović Milan B. (Halo 194)
Introduction: All cardiac conditions that cause the left or right hemilarynx palsy can be defined as Ortner's syndrome. Case Presentation: A 57-year-old man was urgently admitted to the Cardiology Department for laboured breathing and a clinical suspicion of heart failure. An emergency consultation by an otorhinolaryngologist was sought because he was complaining of a choking sensation in addition to hoarseness. Fiberoptic nasopharyngolaryngoscopy revealed restricted mobility of his left hemilarynx. His ECG tracing showed signs of chronic heart failure. Computed tomography of the neck and chest with intravenous contrast confirmed cardiomegaly with mediastinal structure displacement. Betablockers, diuretics, angiotensin receptor blockers, and allopurinol were prescribed, resulting in improved breathing. Conclusion: Hoarseness can be an initial sign of a potentially lethal illness. Early recognition and treatment of the underlying cardiovascular condition are crucial for the patient's recovery. It is essential to emphasize that a dyspneic patient requires a thorough cardiac assessment as well as an examination by an otorhinolaryngologist.